Knowledge and habits of sun exposure in university students: a cross-sectional study in Southern Brazil - Dallazem, Lia Natália Diehl (An Bras Dermatol, 2019)
BACKGROUND: Excessive sun exposure is the major risk factor for skin cancer. Thus, sun exposure behavior is the major focus for prevention of this disease, since it is potentially modifiable. Increasing the knowledge on sun related habits and other skin cancer risk factors is fundamental in the development of preventive programs, especially when directed to young people. OBJECTIVES: To assess the photoprotection habits and the knowledge about skin cancer in college students. METHODS: We conducted a cross-sectional study from Oct. 16 to Feb. 17, including 371 students from the Federal University of Santa Maria, RS, Brazil, through a self-administered questionnaire. RESULTS: The level of knowledge about skin cancer and photoprotection was unsatisfactory in more than 10% of the students. The occurrence of sunburn was extremely high among students, and 25% reported at least one episode of second degree sunburn. Proper use of sunscreen was referred by only 34% of individuals. Students who reported having received photo education in college were associated with a more consistent use of sunscreen. STUDY LIMITATIONS: health area represented a large part of the sample; instrument validated outside Brazil. CONCLUSIONS: Young people are unaware of basic information about sun protection and exposure. Even among those with proper knowledge, the use of photoprotective measures is very low. The sun exposure has shown to be excessive in most of the students, which makes this population an important target for photo-educational measures.